Volcanic ash from Puyehue-Cordón Caulle Volcanic Complex and Calbuco promote a differential response of pro-inflammatory and oxidative stress mediators on human conjunctival epithelial cells - Tesone, Agustina I. (2018)
Volcanic ash could pose a hazard to the ocular surface as it is constantly exposed to environmental particles. We exposed conjunctival cells to Puyehue-Cordón Caulle volcanic complex (PCCVC) or Calbuco ash particles and evaluated proliferation, viability, apoptosis, MUC1 expression, pro-inflammatory cytokines, and oxidative stress markers. Ash particles from these volcanoes vary in size, composition, and morphology. Our results demonstrate that PCCVC but not Calbuco ash particles induce cytotoxicity on human conjunctival epithelial cells viewed as a decrease in cell proliferation and the transmembrane mucin MUC1 expression; a pro-inflammatory response mediated by IL-6 and IL-8; and an imbalance of the redox environment leading to protein oxidative damage. This is the first in vitro study that assesses the biological effect of volcanic ash particles on human conjunctival epithelial cells and the involvement of inflammatory mediators and oxidative stress as the mechanisms of damage. Our results could provide a better understanding of the ocular symptoms manifested by people living near volcanic areas.